Poetry, Philosophy and Madness in Plato - Boysen, Benjamin (Res Cogitans, 2018)
Plato’s unease with the (mimetic) poets is well-known from his expulsion of them from his city-state in The Republic, where they embody the very inversion of philosophical self-understanding. Philosophy – which is guided by reason (λόγος), wisdom (σοφία), and self-control (σωφροσύνη) – is here (and elsewhere in his works) seen to find itself in the highest opposition to poetry inasmuch the latter dangerously provokes desire (ἔρος), pleasure (ἡδονή), and madness (μανία). Here philosophy is understood as a praxis of reason, establishing an ideal, active, and self-determined homogeneity opposed to poetry, understood as an illusory, passive, and alienated heterogeneity. However, poetry is more positively presented in Phaedrus (and to some extent in Ion). Things seem to have been turned upside-down, since philosophy now is presented as a twin brother to poetry, as both originate from god given madness.